Impacts of rotating surface and area expansion during nanofluid convection on phase change dynamics for PCM packed bed installed cylinder - Ghachem, Kaouther; Selimefendigil, Fatih; Öztop, Hakan Fehmi; Alhadri, Muapper; Kolsi, Lioua; Alshammari, Naif (Elsevier, 2022)
Phase change dynamics under the rotational surface effects, area expansion and nanoparticle loading in the base fluid are explored for forced convective flow of hybrid nanofluid in a phase change packed bed installed cylindrical reactor. The study is performed with finite element method for different parameters of rotational Reynolds number, fluid stream Reynolds number and concentration of nanoparticle. The hybrid nanofluid properties are based on experimental data for binary particle of Al2O3-TiO2 in 40% ethylene-glycol. Complete phase transition time is estimated with ANFIS based model. The recirculation zone due to the area expansion within the phase change installed region is controlled by the complex interactions between the forced flow, rotation of the surface and nanoparticle amount. Higher values of Reynolds number and nanoparticle concentration result in fast phase change process at rotational Reynolds number of 0 while the effects become reverse in the presence of rotations. Complete phase transition time reduces by about 49% and 10.5% at the highest Reynolds number and at the highest concentration in the absence of rotation while it is increased by about 88% and 6.5% when rotational effects are considered at the highest rotational speed. When only rotational effects are considered, phase change process completion time reduces by about 60% at the highest speed. (C) 2021 THE AUTHORS. Published by Elsevier BV on behalf of Faculty of Engineering, Alexandria University.
Keywords: Phase change material; Area expansion; Rotations; Finite element method; Adaptive-network based fuzzy inference; Nanotluids